Estudio comparativo de implantes de superficie lisa y rugosa. Resultados a 36 meses (2010)
ABSTRACT: The implant surface affects the clinical response in terms of osseointegration and should be evaluated in the long term. In the last years, literature has strongly recommended the use of modified